Aceclofenac in rheumatology: The golden mean - Andrei Evgenyevich Karateev (Современная ревматология, 2013)
Effective pain relief is an essential component of combination therapy for rheumatic diseases (RD). Amongst analgesics, there are nonsteroidal anti-inflammatory drugs (NSAIDs) that hold a central position. Nineteen different representatives of this group are currently used in Russia, which allows the most appropriate medication to be chosen for each clinical situation and a specific patient. The primary difference between NSAIDs is their safety. There are two polar groups of NSAIDs: 1) nonselective COX-2 inhibitors (nNSAIDS) that rather frequently cause complications in the gastrointestinal tract (GIT), but are safer for the cardiovascular system; and 2) highly selective COX-2 inhibitors (coxibs) that are, on the contrary, characterized by a lower risk for GIT disease, but a higher risk for cardiovascular events. Aceclofenac, a drug that has moderate COX-2 selectivity, holds a good position between nNSAIDs and coxibs, which makes its use advisable for most patients with RD. Clinical trials and epidemiological studies show that both the GIT and cardiovascular system well tolerate the drug. This review gives the basic data pertaining to the evaluation of the safety of aceclofenac, including the results of the last (2012) meta-analysis of population-based studies of the risk of GIT bleeding due to the use of various NSAIDs and those of the AEROPLAN Russian study (of aceclofenac versus nimesulide).